Characteristics and mechanisms of air-core vortex meandering in a free-surface intake flow. (July 2022) - Zi, Dan; Shen, Lian; Wang, Fujun; Wang, Benhong; Yao, Zhifeng
Abstract: The air-core vortex generated at hydraulic intakes is usually associated with efficiency reduction and performance deterioration of the hydraulic machinery. Numerical simulations of the air-core vortex in a horizontal intake system are performed for various intake submergence depths and flow rates. Our study focus on the characteristics and mechanisms of the air-core vortex meandering phenomenon. Statistical analyses of the meandering coordinates of the vortex core are carried out, which characterize the meandering scope, dispersion radii and frequencies of the meandering coordinates of the air-core vortex. Parametric studies of the effects of the flow parameters on the air-core vortex meandering indicate that the dispersion radii increase as the intake flow rate increases or the intake submergence depth decreases, and the meandering frequencies decrease with increasing flow rate. Snapshot proper orthogonal decomposition (POD) analyses of the velocity and vorticity fields reveal that the large-scale energetic coherent structures in the first two modes cause streamwise and spanwise displacement of the air-core vortex, and the small-scale coherent structures with low energy fractions in the third to sixth modes contribute to elliptical deformation of the vortex core. Multiple relationships among the temporal frequencies of the decomposed POD modes and the meandering coordinates are discovered, which further proves that the large-scale energetic coherent structure in the turbulent flow field is the intrinsic reason for the meandering phenomenon of the air-core vortex. Highlights: Characteristics of air-core vortex meandering in a free-surface intake flow are elucidated. The large-scale energetic coherent structures in the first two modes cause air-core vortex meandering. The small-scale coherent structures contribute to elliptical deformation of the vortex core. Multiple relationships among the temporal frequencies of the decomposed POD modes and the meandering coordinates are discovered.